Konstruksi Plasmid Pengekspresi Antigen Gag dan Protein Penghantar VP22 untuk Pengembangan Vaksin HIV-1 - Melinda Remelia; Budiman Bela; Silvia Tri Widyaningtyas; Fera Ibrahim (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
The endogenous HIV-1 vaccine based on Gag protein is expected to stimulate the immune response of CD8+ T cells (cytotoxic). The Gag protein that has been produced by the E.coli prokaryote system is an exogenous antigen. The fusion of VP22 protein is expected to deliver Gag antigen into the cytoplasm of cell, observed by eGFP markers. Sequences of VP22 (114 pb), GagHIV-1 (1506 pb), and eGFP (733 pb) were inserted into the pQE80L, respectively. The recombinant protein was expressed in the E.coli system and purified by the Ni-NTA method. Antigen delivery fused with VP22 and eGFP was observed with fluorescence and confocal microscopy. The recombinant plasmid constructs of protein expression eGFP, VP22-eGFP, GagHIV-1-eGFP, VP22-GagHIV-1-eGFP were verified by DNA sequencing according to the reference. The recombinant plasmid constructs of Gag HIV-1-eGFP and VP22-GagHIV-1-eGFP still need to be optimized so they can be expressed in the E.coli system. The recombinant protein VP22-eGFP (27.02 kDa) was succesfully obtained and fluorescent green (entered) into the cytoplasm and nucleus of vero cells. In addition to the HIV-1 vaccine, this recombinant plasmids pQE80L-eGFP and pQE80L-VP22-eGFP also have the potential to be used as tools in the development of endogenous vaccines for another viruses/microbes. Abstrak Vaksin endogen HIV-1 berbasis protein Gag diharapkan dapat menstimulus respons imun sel T CD8+ (sitotoksik). Protein Gag yang telah diproduksi dengan sistem prokariota E.coli merupakan antigen yang bersifat eksogen. Fusi protein VP22 diharapkan mampumenghantarkan antigen Gag masuk ke sitoplasma sel, diamati dengan marker eGFP. Sekuens VP22 (114 pb), GagHIV1 (1506 pb), dan eGFP (733 pb) telah diinsersikan pada vektor pQE80L. Protein rekombinan diekspresikan pada sistem E.coli dan dipurifikasi dengan metode Ni-NTA. Penghantaran antigen yang difusikan dengan VP22 dan marker eGFP diamati dengan mikroskop fluoresens dan konfokal. Konstruksi plasmid rekombinan pengekspresi protein eGFP, VP22-eGFP, GagHIV1-eGFP, dan VP22-GagHIV1-eGFP telah diverifikasi dengan sekuensing DNA sesuai dengan sekuen referensi. Plasmid rekombinan pengekspresi GagHIV1-eGFP dan VP22-GagHIV1-eGFP masih perlu dioptimasi agar dapat diekspresikan di sistem E.coli. Protein rekombinan VP22-eGFP (27,02 kDa) telah berhasil diperoleh serta berpendar fluoresens hijau (masuk) ke sitoplasma dan nukleus sel vero. Selain vaksin HIV-1, plasmid rekombinan pQE80L-eGFP dan pQE80L-VP22-eGFP juga berpotensi dapat digunakan sebagai ‘tools’ dalam pengembangan vaksin endogen dari virus atau mikroba lainnya.